Econometric Analysis of Acceptance of Soil and Water Conservation Techniques in the Semiarid Region of Zaghouan (North-East Tunisia) - Gara, Anissa; Hammami, Mohamed; Hammami, Sofiene; Aounallah, Mohamed Karim; Elmouaddab, Rabeb; Nahdi, Mariem; Laajili-Ghezal, Lamia (Asian Journal of Agriculture and Rural Development, 2020)
The Tunisian government has established some strategies to face soil erosion. In this research, we aim to study the perception of farmers towards these conservation structures in terms of the acceptability of installation of these amenities and terms of their maintenance. We try to define the socio-economic variables that explain why some farmers in the study area accept the installation of soil conservation facilities while others do not and at what rate of maintenance. Therefore, we used Tobit and Probit models to examine respectively the probability of acceptance of conservations amenities (agreement of farmers that conservation techniques be implemented on their lands) and the rate of acceptance (allocation of land for maintained CTs). It comes out that the factors affecting CTs acceptance are land size, animal husbandry, irrigation from the lake, and land tenure.